Household food coping strategies during the COVID-19 pandemic in Padang City - Risti Kurnia Dewi; Firdaus Firdaus; Salsabil Naqiyyah; Sheisvi Noviaresika Putri (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The COVID-19 pandemic has negatively impacted life sectors, including food access. It drives people to make some responses called food coping strategies to adapt to the current situation to fulfill their food access. This study aimed to analyze some of the food coping strategies done by households in Padang City during the pandemic. It was a descriptive study involving 87 households in Padang City located in the working areas of Anak Air, Lubuk Buaya, and Seberang Padang Health Center. Data on household characteristics and food coping strategies were collected through direct interviews. Data analysis showed a decrease in the household economic situation, shown by a 7,7% decrease in total expenditure per capita in a group below 40% compared to last year. 65,5% of the households did a tingkat two food coping strategy, and 14,9% even had to do the most extreme. Most of the households did food coping strategies by changing their food habits. We hope that government can evaluate the current policy so that no household has to do the most extreme coping strategies.